"MAITRES ANCIENS" DE NICOLAS MAHLER (D’APRÈS THOMAS BERNHARD) : L’ART À L’ÉPREUVE DE LA CARICATURE - Sylvaine FAURE-GODBERT (Studia Universitatis Babeş-Bolyai. Philologia, 2017)
Old Masters of Nicolas Mahler (after Thomas Bernhard): Art Which Tests the Caricature. Nicolas Mahler, born 1969 in Vienna, is a major figure in the German-speaking world of comics and his graphic novel Old Masters (2011) falls in with his own reflection on art. I will try to identify the devices (options of narrative patterns, graphic style, etc.) thanks to which he aligns this adaptation of a comedy by the Austrian novelist and playwright Thomas Bernhard with his own works. The systematic wrecking of art that the musicologist Reger carries out in his diatribes thus translates in the graphic novel as a radical iconoclasm. Indeed, Reger’s defense of an aesthetic of the fragment as well as his praise for caricature become in Mahler’s adaptation quite an irreverent effort to deconstruct old masters and their works.